Early Infantile Thiamine Transporter-2 Deficiency with Epileptic Spasms—A Phenotypic Spectrum with a Novel Mutation - Mishra, Ranjana; Bijarnia-Mahay, Sunita; Kumar, Praveen; Buxi, Tarvinder Bir Singh; Kulshrestha, Samarth; Kuldeep, Jitendra; Gupta, Deepti; Saxena, Renu; Sabharwal, Rama Kant (Journal of Pediatric Epilepsy, 2021)
Epileptic seizures are a frequent feature of thiamine transporter deficiency that may present as a clinical continuum between severe epileptic encephalopathy and mixed focal or generalized seizures. Thiamine metabolism dysfunction syndrome 2 (MIM: 607483) or biotin-thiamine-responsive basal ganglia disease (BTBGD) due to biallelic pathogenic mutation in the SLC19A3 gene is a well-recognized cause of early infantile encephalopathy with a Leigh syndrome-like presentation and a lesser-known phenotype of atypical infantile spasms. We reported a 4-month-old infant who presented with progressive epileptic spasms since 1 month of age, psychomotor retardation, and lactic acidosis. Magnetic resonance imaging (MRI) revealed altered signal intensities in bilateral thalamic and basal ganglia, cerebellum, brainstem, cortical and subcortical white matter. Whole exome sequencing identified a homozygous ENST00000258403.3: c.871G > C (p.Gly291Arg) variant in the SLC19A3 gene. We elucidate the features in the proband, which were an amalgamation of both the above subtypes of the SLC19A3 associated with early infantile encephalopathy. We also highlight the features which were atypical for either “Leigh syndrome-like” or “atypical infantile spasm” phenotypes and suggest that the two separate entities can be merged as a clinical continuum. Treatment outcome with high-dose biotin and thiamine is promising. In addition, we report a novel pathogenic variant in the SLC19A3 gene.
Keywords: infantile spasms; biotin-thiamine-responsive; encephalopathy; thiamine; transporter; basal ganglia disease